The Effect of Alumina (Al2O3) Volume Fraction and Stir casting Conditions on Porosity and Fatigue Life of Aluminum Matrix Composites (Albayan Scientific Journal, 2024)
Aluminum matrix composites (AMCs) have gained research attention because of their excellent strength to weight ratio. The current paper is focused on mechanical and microstructural characterization of stir cast aluminum (AA6063) matrix composites reinforced with three volume fractions of 150 µm Al2O3 particles. The samples under investigation were created by stir casting at various melting temperatures and stirring speed. Different produced composites were evaluated using tensile strength, porosity, fatigue life, and microscopic examination. The tensile and fatigue tests indicated that the mechanical properties of produced composites are improved as the volume fraction of alumina particles increased. Additionally, porosity levels increased with higher Al2O3 volume fractions but decreased at elevated temperatures. variations in porosity were observed when mixing speed were varied. Microstructural study exposed that Micro- Al2O3 particles were distributed uniformly throughout the matrix.
Keywords: Volume fraction; stir casting; fatigue life; porosity; alumina; aluminum (AA6063); composite material